2020
DOI: 10.1002/jso.25895
|View full text |Cite
|
Sign up to set email alerts
|

Does age influence disease‐specific survival in patients with squamous cell carcinomas of the head and neck?

Abstract: Background and Objectives: The number of patients diagnosed with head and neck squamous cell carcinoma (HNSCC) at an advanced age has increased. The aim of this study is to evaluate the age at which disease-specific survival (DSS) significantly decreases in HNSCC. Methods:We performed a retrospective study of 5469 patients with HNSCC treated at our center . External validation with 2082 oral squamous cell carcinomas from a collaborative institution from another continent was performed. Results:We observed an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…26 CSS at any time is higher in patients with nasopharynx cancer compared to oropharynx or hypopharynx cancers. 27 Our results add to this body of work, whereby patients with salivary gland, oral cavity, and hypopharynx cancer have worse 2-year CSS compared to patients with oropharynx cancer. Fitness for operation is an important patient factor which influences hypopharyngeal CSS 1 ; however, our results demonstrate that this feature may also be important in other head and neck subsites, warranting further investigation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…26 CSS at any time is higher in patients with nasopharynx cancer compared to oropharynx or hypopharynx cancers. 27 Our results add to this body of work, whereby patients with salivary gland, oral cavity, and hypopharynx cancer have worse 2-year CSS compared to patients with oropharynx cancer. Fitness for operation is an important patient factor which influences hypopharyngeal CSS 1 ; however, our results demonstrate that this feature may also be important in other head and neck subsites, warranting further investigation.…”
Section: Discussionsupporting
confidence: 60%
“…Larynx patients also have improved 5‐year CSS when compared to oral cavity patients at 5 years 26 . CSS at any time is higher in patients with nasopharynx cancer compared to oropharynx or hypopharynx cancers 27 . Our results add to this body of work, whereby patients with salivary gland, oral cavity, and hypopharynx cancer have worse 2‐year CSS compared to patients with oropharynx cancer.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, only 2% of patients between 45 and 60 without comorbidities do not receive a guideline-based therapy, whereas more than 10% of patients older than 70, also without comorbidities, are treated with non-standard therapies [ 7 ]. In this context, one must keep in mind that chronological age should not prevent patients from receiving curative treatment [ 9 ]. The comorbidities that increase the probability of treatment-related adverse events and predict a disadvantageous outcome are of higher importance [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies often define elderly age starting at 65-70 years old despite evidence showing significant decrease in HNSCC survival starting at 80 years old. 13 There is limited data looking specifically at patients over the age of 80. One study looking at treatment outcomes for locally advanced (stage III and IV) HNSCC in patients over the age of 80 found poor median survival, calling into question whether treatment is futile for elderly patients with locally advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…Though studies have observed acceptable tolerance to curative treatment in elderly patients, most studies vary in what constitutes an elderly patient. Studies often define elderly age starting at 65–70 years old despite evidence showing significant decrease in HNSCC survival starting at 80 years old 13 . There is limited data looking specifically at patients over the age of 80.…”
Section: Introductionmentioning
confidence: 99%